Statistics of High-Technology Manufacturing: Methodological Foundations - Salikhova, O. B. (Statistics of Ukraine, 2025)
The article explores the historical evolution and methodological transformation of approaches to classifying high-tech industries and assessing their contribution to economic development. Drawing on scientific works that have analyzed this topic since the 1950s, the author examines the transition from qualitative assessments of technological progressiveness to quantitative measurements based on the indicator of research and development (R&D) intensity (the ratio of R&D expenditures to value added or sales). Methodological approaches developed by scholars and international organizations are discussed, and normative threshold values for identifying high-tech industries are presented.Particular attention is given to the limitations of the sectoral approach, which predominantly relies on input indicators – such as R&D expenditures and the share of scientific and technical personnel – and insufficiently accounts for qualitative and institutional factors that influence innovation dynamics. The article also highlights conceptual contradictions arising from the assumption of technological homogeneity within industries, as well as methodological distortions caused by defining high-tech industries solely based on aggregated statistical indicators without considering intra-industry heterogeneity or the innovation activity of individual enterprises. It is emphasized that high R&D expenditures do not always reflect the actual enhancement of technological potential, as part of these expenditures may be directed towards non-technological measures, such as loss prevention, while low-tech industries may produce goods based on advanced technologies.To overcome these limitations, a comprehensive, multi-dimensional resource-output approach to evaluating high-tech production is proposed. This approach combines quantitative and qualitative indicators, incorporating the diagnosis of an enterprise’s technological potential, the analysis of measures to strengthen it, and the assessment of the effectiveness of these measures and the overall performance of the enterprise through the category of “overall quality”.The author outlines practical measures for Ukraine, including recommendations for developing methodologies for the identification and certification of high-tech enterprises, creating state registers of such enterprises, and implementing a multi-dimensional form of state statistical reporting that combines both quantitative and qualitative indicators to monitor their activities. These measures, especially under conditions of limited resources and time, could serve as the foundation for implementing a targeted approach to innovation stimulation, the formation of national technological champions, and the enhancement of Ukraine’s international competitiveness, which is particularly relevant in the context of post-war economic recovery.